Statistical Analysis of Rainfall Insurance Payouts in Southern India - Giné, Xavier; Townsend, Robert; Vickery, James (World Bank, Washington, DC, 2012)
Using 40 years of historical rainfall data, this paper estimates a distribution for payouts on rainfall insurance policies offered to farmers in the State of Andhra Pradesh, India, in 2006. The authors find that the contracts primarily protect households against extreme tail events; half the expected value of indemnities paid by the insurance are generated by only 2 percent of rainfall realizations. Contract payouts are significantly correlated cross-sectionally, and also inversely associated with real GDP growth. The paper discusses the implications of these findings for the potential benefits of insurance to households, the risks facing a financial institution underwriting rainfall insurance contracts, and pricing.